Challenging cases in cataract surgery [ - Afshari, Natalie A.; Henderson, Bonnie A. (Expert management DVD series, 2009)
Presents a selection of common and challenging cases in cataract surgery and demonstrates possible techniques, novel technologies, and management strategies for these cases